Hyperbaric Oxygen Therapy in Retinal Arterial Occlusion: Epidemiology, Clinical Approach, and Visual Outcomes. (28th December 2019) - Lopes, Ana Sofia; Basto, Rita; Henriques, Susana; Colaço, Luísa; Costa e Silva, Filomena; Prieto, Isabel; Guerreiro, Francisco
Abstract : Purpose. To evaluate the efficacy and safety of hyperbaric oxygen therapy (HBOT) in patients with acute retinal artery occlusion (RAO). Secondarily, to analyse the epidemiology and the clinical approach. Methods. Retrospective study of 13 patients submitted to HBOT between 2013 and 2018. The analysed parameters consisted of: systemic history, time between symptoms onset and treatment, initial approach, number of HBOT sessions, complications of HBOT and best corrected visual acuity—BCVA (of the total sample, central RAO—CRAO—group, and branch RAO—BRAO group). Results. Arterial hypertension was the most prevalent systemic risk factor (53.8%). Initial therapies were 100% normobaric oxygen administration, topical and oral hypotensive medication, eye massage and aspirin. CRAO was observed in 69.2% and BRAO in 30.8% of the cases, with clinically significant visual improvement (a decrease in logMAR of 0.3) in 55.5% and 75%, respectively. Time between symptoms onset and treatment had a median of 9 hours. The median number of HBOT sessions was 7, without complications. Conclusions. HBOT provide BCVA improvement in patients with RAO, when it is performed in an early time after the symptom onset. It seems to be an effective and safe therapeutic option for a pathology that still remains without approved treatment.